Renewable Energy Potential in Selected Countries - World Bank (Washington, DC, 2014)
Renewable energy (RE) resources have been attracting growing interest in both the industrialized and the developing world in the last five to eight years. The main drivers for this interest and accelerated activity have been the expected strong demand for energy in the developing world and environmental concerns, particularly of the risk of drastic climate change as a result of the increasing accumulation of greenhouse gases in the atmosphere. Volume 1 covers : North Africa region, countries of Central Europe and the former Soviet Union (FSU). Volume 2 : Latin America. The decision to conduct regional rather than specific country studies was made to take into account the commonalities of the shared characteristics of a group of countries. Some of the results and conclusion of the study regarding countries of Central and Eastern Europe, as a group, certain regional aspects emerge. First, they all share the legacies of the Soviet Union, notably in their economic structure, mentality, and methodologies. Second, they depend on each other for a number of goods and services and are trying to transition to a modus operandi appropriate to a market economy framework. The development of regional markets would be a natural outcome of this effort on the supply side. Volume 2 covers progress in the use of renewable energy for rural electrification being made in select countries in the LAC Region, with other countries anxious to learn from and follow successful development models. Chapter 2 highlights the in-depth efforts underway in Argentina, as well as the vast market potential for renewable technologies and rural electrification throughout Mexico. Finally, while smaller in scale, the case of Panama offers an insight into a country committed to providing a framework and implementation strategy that focuses on both renewable energy and rural electrification.